2023
DOI: 10.1371/journal.pmed.1004135
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle behaviors, mediating biomarkers, and risk of microvascular complications among individuals with type 2 diabetes: A cohort study

Abstract: Background The influence of overall lifestyle behaviors on diabetic microvascular complications remains unknown. In addition, the potential mediating biomarkers underlying the association is unclear. This study aimed to examine the associations of the combined lifestyle factors with risks of total and individual microvascular complications among patients with type 2 diabetes (T2D) and to explore the potential mediation effects of metabolic biomarkers. Methods and findings This retrospective cohort study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 50 publications
1
35
0
1
Order By: Relevance
“…Meanwhile, because adherence to a healthy lifestyle can also reduce the risk of hypertension (32, 33), people without hypertension are recommended to follow a healthy lifestyle as well. Furthermore, due to the potential mediating effect of lipid profile on lifestyle and CVD (34), lipid was not included as a confounder in models, which was consistent with other studies (13,(28)(29)(30).…”
Section: Comparison With Other Studiessupporting
confidence: 67%
“…Meanwhile, because adherence to a healthy lifestyle can also reduce the risk of hypertension (32, 33), people without hypertension are recommended to follow a healthy lifestyle as well. Furthermore, due to the potential mediating effect of lipid profile on lifestyle and CVD (34), lipid was not included as a confounder in models, which was consistent with other studies (13,(28)(29)(30).…”
Section: Comparison With Other Studiessupporting
confidence: 67%
“…In this issue of PLOS Medicine , an accompanying study by Tingting Geng and colleagues provides a new perspective on the association of overall lifestyle factors with the risk of microvascular complications [ 7 ]. This retrospective study included 15,104 people with type 2 diabetes free of macro or microvascular complications at baseline from the UK Biobank.…”
mentioning
confidence: 99%
“…Thus, the 2 observational studies taken from different study populations give us confidence in the positive findings of lifestyle interventions in the prevention of microvascular complications. However, both highlight that there is an extremely low number of people with diabetes who adhere to a healthy lifestyle: in the new study, Tingting Geng and colleagues found only 10.3% were adherent to 4 to 5 low-risk lifestyle behaviours in UK Biobank [ 7 ]. Similarly, Zhijia Sun and colleagues found only 14.4% were adherent in the Chinese Kadoorie Biobank [ 8 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations